Cloning and in silico and expression analyses of the heterotrimeric G protein α subunit gene (EjLGA1) from loquat (Eriobotrya japonica) fruits under cold storage with different pretreatments. Issue 3 (4th May 2019) - Wu, Ti; Lin, Shoukai; Wu, Bisha; Chen, Yu; Lin, Suying; Lin, Dahe; Chen, Linxia; Zhang, Zhisheng; Wu, Jincheng
ABSTRACT: Cold-stored fruits of the loquat ( Eriobotrya japonica Lindl.) plant suffer from strong lignification, which leads to a hard texture and a crude mouthfeel of the pulp. However, the signalling mechanisms of loquat fruits under cold storage remain unclear. In this study, the heterotrimeric G protein α subunit (Gα) gene ( EjLGA1 ) from loquat was isolated, and in silico analysis was performed. The levels of EjLGA1 expression in cold-stored loquat fruits with different pretreatments were also investigated. The largest open-reading frame of EjLGA1 is 1173 bp, encoding a polypeptide of 390 amino acids. The nucleotide and amino acid sequences of the Gα subunit are highly conserved among loquat and 48 other seed plants, indicating that the loquat Gα subunit likely has similar functions in other plants. A reliable model of the loquat Gα subunit was constructed, which revealed the structure of the subunit. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) results showed that EjLGA1 is highly expressed under cold storage, which suggests the significance of EjLGA1 function in loquat fruits in response to cold stress. However, ethephon and 1-methylcyclopropene (1-MCP) pretreatments did not regulate EjLGA1 expression. These results provide new insight into the signalling mechanism in cold-stored loquat fruits.